AUDIOLOGY science to practice. - Kramer, Steven J.; Brown, David K. (Professor of audiology) (PLURAL PUBLISHING INC, 2021)
With two new chapters, improved artwork, and significant updates made throughout, the fourth edition of Audiology: Science to Practice continues to be the most comprehensive textbook for audiology and hearing science courses, as well as for health care professionals wanting a better understanding of hearing science and audiology practices. It is written in a style that makes new or difficult concepts relatively easy to understand, while still providing more coverage of hearing and vestibular science and clinical audiology than other introductory texts.